Impact of Massive Transfusion and Aging Blood in Acute Trauma. Issue 10 (October 2016) - Anand, Tanya; Ramnanan, Rajesh; Skinner, Ruby; Martin, Maureen
Blood transfusions cause altered immunity and the duration of storage is contributory. In the era of massive transfusion protocols (MTPs) this impact is unclear, particularly as it relates to balanced transfusions. Trauma patients requiring our MTP after admission to our Level II trauma center were studied. The average age of blood transfused was calculated; old blood was a storage time of ≥14 days versus new blood <14 days. Blood to plasma ratios of 1:1 were compared with ratios >1:1. Infections, organ dysfunction multiorgan injury (MOD, and death were compared based on ratios and blood storage times. Of 2200 trauma admissions, 89 patients required MTP. Penetrating injuries were the majority, n = 53; and Injury Severity Score was 33 ± 14. Overall mortality was 31 per cent and sepsis was 28 per cent. Outcomes (storage time): Patients receiving old versus new blood had comparable age and Injury Severity Score. Sepsis rates, multiorgan injury and mortality were similar. Outcomes (packed red blood cells:fresh frozen plasma): Balanced transfusions (ratios of 1:1) demonstrated significant survival benefit and less infections compared with ratios >1:1. These data underscore the complexity of transfusion-related morbidity. In the modern era of MTP and balanced transfusions, the age of stored blood may not impact outcomes as demonstrated historically.